The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1136/oemed-2013-101475
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre study for the evaluation of mutagenic/carcinogenic risk in nurses exposed to antineoplastic drugs: assessment of DNA damage

Abstract: Although stringent rules were adopted at national and international levels to prevent occupational exposure to antineoplastic drugs, data reported in this study support the idea that a more efficient survey on long-lasting exposures at very low concentrations is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
4
28
1
1
Order By: Relevance
“…In a recently published paper (Buschini et al 2013), we have reported on the extent of primary, oxidative, and "cryptic" DNA damage as evaluated by comet assay in circulating leukocytes from the same nurses (exposed and controls) evaluated herein for cytogenetic damage. In such earlier work, we did not observe any statistically significant difference between exposed nurses and control subjects when primary DNA damage was evaluated in leukocytes (i.e., alkaline comet assay).…”
Section: Discussionmentioning
confidence: 97%
“…In a recently published paper (Buschini et al 2013), we have reported on the extent of primary, oxidative, and "cryptic" DNA damage as evaluated by comet assay in circulating leukocytes from the same nurses (exposed and controls) evaluated herein for cytogenetic damage. In such earlier work, we did not observe any statistically significant difference between exposed nurses and control subjects when primary DNA damage was evaluated in leukocytes (i.e., alkaline comet assay).…”
Section: Discussionmentioning
confidence: 97%
“…Epidemiological studies of personnel who handle antineoplastic drugs, performed on a global scale, showed detectable levels of genotoxic drugs in the work environment and a statistically significant increase in DNA damage and chromosomal aberrations in the exposed population versus the reference group (Buschini, 2013). Other studies have found increased chromosomal aberrations and evidences of mutagenic/carcinogenic risks in urine samples of exposed nurses (Shahrasbi et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Antineoplastic or cytostatic drugs are a heterogeneous group of widely used therapeutics for neoplastic and non-neoplastic diseases. However, these drugs have been proved to be also mutagens, carcinogens, and teratogens (19)(20)(21)(22)(23)(24)(25).…”
Section: Antineoplastic Drugs In Cancer Treatmentmentioning
confidence: 99%
“…According to the European Guidelines (74), any use of carcinogenic, mutagenic or teratogenic substances, including the application in health care settings, is assigned to the highest risk level (20)(21)(22)(23)75). Based on epidemiological reports, animal carcinogenicity data, and the outcomes of in vitro genotoxicity studies, several antineoplastic drugs have been classified by the International Agency for Research on Cancer (IARC) as belonging to the group of human carcinogens (Group 1), probable human carcinogens (Group 2A), or possible human carcinogens (Group 2B) (76,77).…”
Section: Occupational Exposure To Antineoplastic Drugsmentioning
confidence: 99%